Book Review: Davidson’s Principles and Practice of Medicine, 19th edition (Res Medica, 2014)
The first edition of Davidson’s appeared in 1952; an almost pocket-sized volume which promised to concentrate on common disorders and everyday problems illustrated by an account of the applied anatomy and physiology of the relevant system. The textbook has come a long way since then, but remains true to its original ideals.